SISTEM PENUNJANG KEPUTUSAN KENAIKAN JABATAN MENGGUNAKAN METODE WEIGHTED PRODUCT PADA PT HASTA KARYA SEJAHTERA - Teguh Purnomo; Luqman; Rahayu Widayanti (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2024)
Hasta Karya Sejahtera engaged in the installation and management of electricity in cooperation with PLN. PT Hasta Karya Sejahtera serve new electrical installation, termination and connection of electricity, and electicity payment online. The problems that exist in PT Hasta Karya Sejahtera is still using the performance appraisal form manually. The research objective is to simplify the Field Personel in assessing the promotion so as to provide objective information and trasparency to the leadership. Data collection methods used were interviews and survey, while. System development method used is the waterfall method. System Decision Support promotion appraisal using weighted product method can simplify the field personel in assessing the promotion so as to provide objective information and transparency to the leadership.